Mini Med School: Why you should try a virtual, medical student-led program - Cameron, Nicole H; De Pieri, Julia; Smith, Drew H; Gair, Jane (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2023)
Implication StatementMini Med School (MMS) programs led by medical students provide a unique opportunity for community members to access free and accurate health information while engaging with the education of medical students. Virtually delivered MMS programs reduce barriers to access. 90.3% of participants in a recent MMS enjoyed medical students delivering the seminars. 63.6% of participants preferred virtual MMS seminars, with 31.8% preferring a combination of virtual and in-person delivery. Student-led, virtually delivered MMS programs are an engaging way to support both medical student and community education while strengthening community ties with local medical schools.